Rotation of both X- and Y-axes is a predictive confounder of ulnar nerve injury and open reduction in pediatric lateral flexion supracondylar humeral fractures: A retrospective cohort study - Sun, Jun; Shan, Jing; Meng, Lian; Liu, Tianjing; Wang, Enbo; Jia, Guoqiang (Frontiers in Pediatrics, 2022)
Background: Rotation of distal fragment often occurs in flexion-type supracondylar humerus fractures (SCHFs), potentially leading to ulnar nerve injury (UNI) and open reduction. We analysed the correlation between the rotations and UNI or open reduction, and then assessed the risk factors associated with the rotations. Methods: Data of Wilkins type Ⅲ lateral flexion SCHFs were collected over a ten-year time-period (January 1, 2012 to December 31, 2021) in Children’s Hospital of Fudan University Anhui Hospital. We defined the rotation of distal fragment on coordinate axis as two types, ⅢA ( X-axis rotation) and ⅢB (both X&Y-axis rotation) on X-ray radiography. The demographic data, incidence of the two types rotation, odd ratios (ORs) of UNI and open reduction, and risk factors of both X&Y-axis rotation were analysed. Results: Totally, 152 patients were found (50 with ⅢA versus 102 ⅢB). The UNI rate was 13% and the open reduction rate was 22%. The UNI rate of ⅢB was 5-fold higher than of the ⅢA (OR, 5.143; 95%CI, 1.414-23.125; p=0.019), and the open reduction rate of ⅢB was nearly 5-fold higher than of the ⅢA (OR, 4.729, 95%CI, 1.584-14.495; p=0.003). In the two types, the patients with UNI had a higher risk of open reduction than those without UNI (OR, 9.816; 95%CI, 3.503-27.508; p=0.001). On the multiple regression analysis, the high lever fracture was identified as a risk factor of both X&Y-axis rotation. Conclusion: The ⅢB type lateral flexion-type SCHFs are with higher UNI and open reduction rates, and the high lever fracture is a risk factor associated with this type.